Efforts to Improve Learning Outcomes of Aqidah Akhlak with the Index Card Match Method for Class III Students of MI Ma'arif 01 Cilopadang - Lailatul Fajriyah; Icih Aoliah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the learning outcomes of Akidah Akhlak through the application of the Index Card Match method in class III students of MI Ma'arif 01 Cilopadang in the 2024/2025 academic year. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were class III students of MI Ma'arif 01 Cilopadang. The research data were obtained through observation, learning outcome tests, and interviews with students and teachers. The data analysis techniques used in this study were qualitative and quantitative descriptive analysis. The results of the study showed that the application of the Index Card Match method can increase student activity in learning, improve understanding of the concept of Akidah Akhlak, and significantly improve student learning outcomes.